Diglossia and the dominance of words in Kurdish - سعید, پ.ى.د.سازان ظاهر; مەعرووف, پ.د.عەبدولجەبار مستەفا (Sulaimani Journal for Humanities, 2025)
The research is entitled “Diglossia and Word Dominance in Kurdish Language”. The aim of this research is to work to appreciate Diglossia as a phenomenon of linguistic diversity within the framework of sociolinguistics, while discussing and interpreting the phenomenon in relation to Kurdish culture and grammar. There is a favorable environment for the phenomenon at the individual and group levels and it is reflected in conversational groups. The study focuses on the impact of linguistic aspects on diglossia and looks for the consequences that diglossia can have on the speaker's culture and grammar, according to the social position, mental structure, linguistic awareness and the speaker's authority over one or more skills. listening) varies from person to person. In the study, the analytical praise approach was followed. To provide evidence, the samples were taken from the Sulaimani dialect and the speakers of that region were used as criteria
Keywords: Linguistic bilingualism; word dominance; speech groups; monolingualism; bilingualism; linguistic consciousness